Analisis kesehatan bank dengan menggunakan metode RGEC pada bank umum syariah di Indonesia - Maria ulfa; Muhammad Salman; Mayang Murni (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study aims to determine the health level of Islamic banks at Islamic Commercial Banks using the RGEC method, which includes Risk Profile, Good Corporate Governance, Earning (Rentability) and Capital (Capital). This study uses a quantitative method sourced from secondary data from Islamic Commercial Bank financial reports for 2015-2022. The data analysis used to determine the health level of banks in this study is descriptive analysis using the RGEC method. The results of the study show that the health level of Islamic Commercial Banks for 2015-2022 is at a composite rank of 1 (PK - 1), which is included in the